(untitled) (Research, Society and Development, 2021)
Seed quality is defined by several factors such as genetic, physical, physiological and sanitary attributes. Even with all good factors involved, germinating power loss occurs. However, this loss may be reduced by performing procedures to maintain quality, as storage local and packaging. Thus, the objective of the work was to identify the best environment and packaging for storing niger seeds by analyzing germination and seedling biometry. Samples were separated according to treatments being three types of packaging: paper bag (permeable), plastic bag (semi-permeable) and glass container (impermeable). All packages were storage in two environment: storage shad and cold chamber. For all evaluations sub-samples were removed of each type of pack and environment being at one day after harvest (control), 30, 60, 90, 120 and 150 days of storage. The work was conducted at Laboratory of Seed Technology of Grand Dourados Federal University (UFGD). The experimental design was completely randomized, in a factorial scheme 6 × 6 (treatments x days of storage), with four replicates of 50 seeds each. Sowing was performed between "germitest" papers and rolls were kept in a germinator at a temperature of 25°C under constant white light, for 10 days. The traits evaluated were: first count of germination, percentage of germination and seedling length. Storage locations and type of packaging interfered significantly to development of niger (Guizotia abyssinica (L.f.) Cass.) seed germination. The best results in germination were found in seeds stored in glass container in storage shed and in plastic bag in cold chamber.